THE BORDERLINE PERSONALITY DISORDER OF ANTONY IN THE DRAMA ANTONY AND CLEOPATRABY WILLIAM SHAKESPEARE - eny suprihandani; thea jacinda (Journal of English Language and Literature (JELL), 2018)
Literature can be analyzed from many perspectives and point of views. By using psychoanalytic approach, this paper attempts to analyze one of the Shakespearean’s characters, Antony in the drama Antony and Cleopatra. The objective is to prove whether Antony truly suffers from Borderline Personality Disorder. Borderline Personality Disorder (BPD) is a personality disorder whose essential features are a pattern of marked impulsivity and instability of affects, interpersonal relationships, and self-image. Psychoanalysis theory is a theory developed by Sigmund Freud that enables to analyze whether a person suffers from a certain mental disease. Using those approaches, the characterization of Antony can be analyzed from his words, thoughts and other character’s opinion about him and then compared to the symptoms of Borderline Personality Disorder (BPD) and then found if they are matched. That Antony suffers from Borderline Personality Disorder can be finally proved.